Streptococcus mutans detection on mother-child pairs using matrix-assisted laser desorption ionization – time of flight mass spectrometry and polymerase chain reaction - Udijanto Tedjosasongko; Dwi Mulia Ramadhaniati; Seno Pradopo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Streptococcus mutans (S. mutans) bacteria mainly cause dental caries in children. These bacteria are not considered oral indigenous bacteria since they are transmitted from people around children during their deciduous teeth eruption. The detection of these bacteria can be used for dental caries prevention in children. Purpose: To determine the strain and serotype of S. mutans by using matrix assisted laser desorption ionization – time of flight mass spectrometry (MALDI-TOF MS) and polymerase chain reaction (PCR) on dental plaque samples taken from mother-child pairs. Methods: Sixteen dental plaque samples of mother-child pairs were cultured on brain heart infusion broth (BHIB) and mitis salivarius bacitracin (MSB) media until S. mutans colony isolates were obtained. Next, the isolates of S. mutans colony were introduced into the target plates of MALDI-TOF MS, and then ionized to become peptide mass fingerprint (PMF). Afterwards, the colony isolates were detected by database software. The detected S. mutans DNA then was extracted by using conventional 727 bp PCR (serotype C). Results: Six strains of S. mutans were detected by MALDI-TOF MS method. Five samples were classified into UA159, two samples were 3SN1, two samples were NFSM1, two samples were 11A1, two samples were U138, two samples were 4SM1, and one sample was classified into another bacterium. Five out of 16 samples were detected by PCR as serotype C (UA159). Conclusion: Six strains of S. mutans were detected, namely UA159, 3SN1, NFSM1, 11A1, U138, and 4SM1, one of them (UA159) was detected as serotype C.